VD_FINDINFO Jug / 2019 / 298 vom 17. Januar 2019 - VD Tribunal cantonal (2019)
INJURE, INDEMNITÉEN GÉNÉRAL, DÉPENS, FRAIS JUDICIAIRES, PARTIE CIVILE, PLAIGNANT, ENQUÊTE PÉNALE, MOYEN DE PREUVE, PRÉSOMPTION D'INNOCENCE | 177 al. 1 CP, 177 CP, 426 al. 1 CPP (CH), 430 al. 1 let. a CPP (CH), 433 CPP (CH)